Topical Advertisements & Brand Mascot- A Strategic Combination For Brand Positioning: Study Of Amul - et. al., Dr. Swati Bisht, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The business world is undergoing a sea change with the introduction of new products and services everyday. Competition is getting stiff and every company is battling for that space in the mind of the customers and thus positioning their offering rightly. Advertising, traditionally played the role of informing, persuading and reminding the customers of the existence of a brand. Over a period of time, innovation in copy and creativity has become an important riding factor for the Advertising has always played a major role in terms of positioning a brand in the mind of a customer. But this battle has only got fiercer with just the brand, differentiating products with more or less the basic ingredients remaining same. Advertisements more or less try to create a differentiation for the product or brand they are promoting but again since most of the basic features remain the same, this becomes a daunting task. The marketers are always on a lookout for attracting and retaining the right set of customers. Some of tested and effective ways to position a brand in the mind of the customer include celebrity endorsements while the others less used ones include topical advertisements (where the current news is drives the advertisements) or a simple advertisement which talks about just the brand using a common person model or a character. This paper aims to understand the role of topical advertising and brand mascots in strategically positioning a brand through topical advertisements. The paper studies the advertisement strategies used by one of the most successful brands offered by AMUL ie. AMUL butter. AMUL Butter uses both brand mascot and topical advertising making it together a powerful strategy for the brand to offer to the target market. A conceptual model is proposed to see how topical advertisements are effective